DHA Mitigates Autistic Behaviors Accompanied by Dopaminergic Change in a Gene/Prenatal Stress Mouse Model. (10th February 2018) - Matsui, Fumihiro; Hecht, Patrick; Yoshimoto, Kanji; Watanabe, Yoshihisa; Morimoto, Masafumi; Fritsche, Kevin; Will, Matthew; Beversdorf, David
Highlights: Gestational stress in stress-susceptible 5-HTT HET KO mouse dams leads to autism-like behaviors in offspring. Our findings also demonstrate increased striatal dopamine in this model. Dietary DHA during gestation mitigates the behavioral effects and dopaminergic changes induced by this model. Abstract: Autism Spectrum Disorder (ASD) is characterized by impairments in social interaction, social communication, and repetitive and stereotyped behaviors. Recent work has begun to explore gene × environmental interactions in the etiology of ASD. We previously reported that prenatal stress exposure in stress-susceptible heterozygous serotonin transporter (SERT) KO pregnant dams in a mouse model resulted in autism-like behavior in the offspring (SERT/S mice). The association between prenatal stress and ASD appears to be affected by maternal SERT genotype in clinical populations as well. Using the mouse model, we examined autistic-like behaviors in greater detail, and additionally explored whether diet supplementation with docosahexaenoic acid (DHA) may mitigate the behavioral changes. Only male SERT/S mice showed social impairment and stereotyped behavior, and DHA supplementation ameliorated some of these behaviors. We also measured monoamine levels in the SERT/S mice after three treatment paradigms: DHA-rich diet continuously from breeding (DHA diet), DHA-rich diet only after weaning (CTL/DHA diet) and control diet only (CTL diet). The dopamine (DA) content in the striatum was significantly increased in the SERT/S mice compared with wild-type (WT) mice, whereas no difference was observed with noradrenaline and serotonin content. Moreover, DA content in the striatum was significantly reduced in the SERT/S mice with the DHA-rich diet provided continuously from breeding. The results indicate that autism-associated behaviors and changes in the dopaminergic system in this setting can be mitigated with DHA supplementation.